Characterization of Electromagnetic Valveless Micropump - M. Q. A Ruslia; Pei Song Chee; Pei Ling Leow (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper presents an electromagnetically-actuated micropump for microfluidic application. The system comprises two modules; an electromagnetic actuator module and a diffuser module. Fabrication of the diffuser module can be achieved using photolithography process with a master template and a PDMS prepolymer as the structural material. The actuator module consists of two power inductors and two NdFeB permanent magnets placed between the diffuser elements. The choice of this actuation principle merits from low operating voltage (1.5 Vdc) and the flow direction can be controlled by changing the orientation of the magnet vibration. Maximum volumetric flow rate of the fabricated device at zero backpressure is 0.9756 µLs-1 and 0.4659 µLs-1 at the hydrostatic backpressure of 10 mmH2O at 9 Hz of switching speed.